Health and Political Engagement - Mikko Mattila, Vesa (Taylor & Francis, 2017)
Social scientists have only recently begun to explore the link between health and political engagement. Understanding this relationship is vitally important from both a scholarly and a policy-making perspective. This book is the first to offer a comprehensive account of health and political engagement. Using both individual-level and country-level data drawn from the European Social Survey, World Values Survey and new Finnish survey data, it provides an extensive analysis of how health and political engagement are connected. It measures the impact of various health factors on a wide range of forms of political engagement and attitudes and helps shed light on the mechanisms behind the interaction between health and political engagement. His text is of key interest scholars, students and policy-makers in health, politics, and democracy, and more broadly in the social and health and medical sciences.